(untitled) (JURNAL ADMINISTRASI PUBLIK, 2020)
study aims to determine the implementation of the policy of the village of Ratatotok-Buyat in the North Sulawesi Province. The theory used in this research is the theory of policy implementation proposed by Edward III: communication, resources, disposition, and bureaucratic structure. This type of research is descriptive qualitative. There are 10 people used as informants in this study and to collect data and search for research data using interviews in this study, after the data are collected and will be analyzed descriptively, in order to get answers about the implementation of the Rataotok-Buyat village boundary policy. After conducting in-depth research and interviews, the results of research on the implementation of the Ratatotok-Buyat village boundary policy in North Sulawesi Province, namely the communication process that occurs in the implementation of the Ratatotok-Buyat village boundary policy to the support of human resources in implementing the Ratatotok-Buyat village boundary policy This policy implementation was not well realized. The regional government needs to re-socialize the Ratatotok- Buyat village boundary policy as stipulated in Permendagri No. 69 of 2016 and the government is even more transparent in every policy issued. Ke Words: Policy Implementation, village boundaries